IMPROVING THE EFFECTIVENESS OF THE COMPANY’S PRICING POLICY - Панова, Каріна (SWorldJournal, 2025)
Increasing the effectiveness of pricing policy within an enterprise remains highly relevant in today’s business environment. Market globalization and the volatility of supply and demand present companies with the challenge of adapting their pricing strate